2023
DOI: 10.1128/cmr.00126-22
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Syphilis: a Review of Global Epidemiology

Abstract: In 2007, the World Health Organization (WHO) launched a global health initiative for the elimination of mother-to-child transmission (MTCT) of syphilis. This condition is highly preventable through antenatal identification of syphilis infection and treatment with penicillin during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Although completely curable, syphilis is a sexually transmitted infection caused by T. Pallidum , which is responsible for a silent epidemic wave worldwide ( 3 , 7 – 9 , 58 , 59 ). Even though it is relatively easy to diagnose syphilis through routine laboratory methods, the tests available around the world still present problems, mainly because the most qualified tests are difficult to access, especially in poorer countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although completely curable, syphilis is a sexually transmitted infection caused by T. Pallidum , which is responsible for a silent epidemic wave worldwide ( 3 , 7 – 9 , 58 , 59 ). Even though it is relatively easy to diagnose syphilis through routine laboratory methods, the tests available around the world still present problems, mainly because the most qualified tests are difficult to access, especially in poorer countries.…”
Section: Discussionmentioning
confidence: 99%
“…Syphilis is an infectious disease caused by Treponema pallidum subsp. pallidum ( T. Pallidum ) infection that can be sexually transmitted (Acquired Syphilis—AS) or through vertical transmission during pregnancy (Congenital Syphilis—CS) ( 1 3 ). Although curable and preventable through barrier methods (such as condoms), syphilis has been neglected and still represents a global public health concern due to inadequate diagnosis and treatment, resulting in morbidity and mortality in newborns and untreated infected people ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…The WHO also reported that “congenital syphilis is the second leading cause of preventable stillbirth globally” and that the WHO is “working towards eliminating mother-to-child transmission of HIV, syphilis and hepatitis B” [ 14 ]. Although some countries such as Cuba, Thailand, Malaysia, Maldives, and Sri Lanka have successfully eliminated congenital syphilis, rates have been rising in most low-to-middle income countries (LMICs) and in some high-income countries (HICs) such as the US, Greece, Japan, and the United Kingdom [ 4 ].…”
Section: Epidemiology Of Syphilismentioning
confidence: 99%
“…Approximately 90% of all syphilis infections are estimated to occur in LMICs with the highest burden in African countries which carry 62% of the global congenital syphilis cases [ 4 , 21 , 22 ]. Although bearing a significant burden of congenital syphilis, there are limited data on risk factors in African countries [ 4 ]. LMICs have a disproportionately high burden of other STIs such as HIV [ 23 ].…”
Section: Epidemiology Of Syphilismentioning
confidence: 99%
See 1 more Smart Citation